2022
DOI: 10.1088/1402-4896/ac7109
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale structures in three species magnetoplasmas with two positive ions

Abstract: The self-organization in a multi-ion plasma composed of electrons and two species of positively charged ions is investigated. It is shown that when canonical vorticities and velocities of all the plasma fluids are aligned, the magnetic field self-organizes to the Quadruple Beltrami state (superposition of four Beltrami fields). The self-organized magnetic and velocity fields strongly depend on the relative strengths of the generalized vorticities, flows, inertia and densities of the plasma species. Thus, it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…[ 38 ] On the other hand, when the inertia of electron species is also taken into consideration, a TB state can be obtained by assuming that ion species have same generalized helicities, [ 40 ] whereas a QB state can be derived when all plasma species have distinct generalized helicities. [ 41 ]…”
Section: Qb Field Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 38 ] On the other hand, when the inertia of electron species is also taken into consideration, a TB state can be obtained by assuming that ion species have same generalized helicities, [ 40 ] whereas a QB state can be derived when all plasma species have distinct generalized helicities. [ 41 ]…”
Section: Qb Field Equationmentioning
confidence: 99%
“…[ 40 ] In the most recent investigation by Ullah et al, it was found that the relaxed state is the QB state when all the plasma species are inertial and have different Beltrami parameters or generalized helicities. [ 41 ] Likewise, the study of Beltrami states has been carried out in electron‐depleted dusty multi‐ion plasmas, which consist of stationary negatively charged dust particles in addition to one positive ion species and two negative ion species. In this plasma model, multi‐Beltrami relaxed states such as DB, TB, and QB have also been formulated and investigated by taking into consideration the inertial effects of both positive and negative ion species and adjusting the generalized vorticities of ion species.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to MHD relaxation, relaxed multifluid plasmas have substantial flow and pressure gradients. When compared to single fluid MHD relaxation, which has only one macroscopic scale, the self-organized state of two or multicomponent plasmas is characterized by multiscale structures (both macroscopic and microscopic structures) [7][8][9][10][11]. The multi-Beltrami relaxed states in plasmas allow for the formation of very novel and complex structures, which are applied to the study of a wide range of physical phenomena that occur in the laboratory and in space.…”
Section: Introductionmentioning
confidence: 99%
“…This state is the linear combination of the four single Beltrami states, which means that four self-organized vortices could be formed. 49,50 The concept of plasma relaxation is not restricted to the typical classical multispecies plasmas found in our universe. The DB, TB, and QB states have recently been widely investigated using thermal, degenerate, and general relativistic effects in multispecies plasmas.…”
Section: Introductionmentioning
confidence: 99%